Preparation Physico-Chemical Characterization and Catalytic applications of Polymer Anchored Dimethylglyoxime Copper (II) Metal Complex - Imtiyaz, Rasool Parrey; Athar, Adil Hashmi (Journal of New Developments in Chemistry, 2014)
Oxidation of 1-Proponol, 1-butanol 1-Hexanol and benzyl alcohol using chloromethylated polystyrene (6% Cross link) DMG (Dimethylglyoxime) copper complex or Poly(S-DVB)-DMG-M Where M= Cu) as catalyst and tert.butylhydroperoxide(TBHP) as oxidant, was studied. The polymer supported Cu Complex was characterized by some physicochemical and spectroscopic methods like elemental analysis IR Scanning electron micrographs (SEM). In the oxidation of 1-propanol, 1-butanol, 1-hexanol and benzyl alcohol. It was found that Product yield of these alcohols corresponding the order 1-Butanal >1-hexanone >Benzyldehyde > 1-Propanone. Kinetic data indicates that catalyst could be recycled without significant degradation of polymer
Keywords: Chloromethylated polystyrene; catalyst; tert-butylhydroperoxide; alcohol oxidation.